Oxidative Deamination of Methylamine by Semicarbazide-Sensitive Amine Oxidase Leads to Cytotoxic Damage in Endothelial Cells: Possible Consequences for Diabetes - Yu, Peter H; Zuo, Dong-Mei (Diabetes (New York, N.Y.), 1993)
Methylamine was observed to be deaminated by several semicarbazide-sensitive amine oxidases, which were prepared from blood and vascular tissues of various species, including humans. Although methylamine itself is relatively nontoxic toward endothelial cells obtained from both human umbilical vein and calf pulmonary artery, it becomes very toxic in the presence of SSAO. SSAO inhibitors (i.e., MDL-72974A) effectively protected the cells from methylamine-SSAO–induced damage. The cytotoxicity seems, therefore, to be a consequence of the deamination of methylamine. Our findings suggest that formaldehyde, the deaminated product of methylamine, may be responsible for these toxic effects. Human serum, which also contains SSAO, was also capable of deaminating methylamine and causing cytotoxicity to cultured endothelial cells. Both methylamine and SSAO circulate in human blood, and their concentrations in the blood of normal healthy subjects are quite close to those required to induce cytotoxicity in tissue-cultured cells. Both SSAO activity and methylamine levels have been reported to be increased in the blood of diabetic individuals. Blood SSAO activity also has been reported to be elevated in the blood of STZ-induced diabetic rats. It is possible, therefore, that an abnormal metabolism of methylamine may be involved in endothelial injury, and that it may subsequently induce atherosclerotic plaque formation and thus be involved in the cardiovascular disorders seen in diabetes.